Evaluation of anxiety and depressive symptoms in a sample of adult patients with cancer at Al-Furat Cancer Hospital/Najaf - Hussein Amer Hussein Al-Saffar; Nibras Alaa Hussain (Medical Journal of Babylon, 2023)
Background: Cancer patients’ mental well-being negatively impact on treatment tolerance, reduces the effectiveness of chemotherapy, prolong hospitalization, increase healthcare cost, would lower life expectancy, and poor quality of life. Objectives: The objectives are to evaluate the rate of anxiety and depressive symptoms across adult cancer patients and to find its association with some sociodemographic factors. Materials and Methods: A cross-sectional study was carried out in Al-Furat Cancer Hospital in Najaf/Iraq, from April 10 to July 10, 2022. All convenient patients who were admitted to the hospital during the study period were included. The data were collected by interviewing the patient using semiconstructed questionnaire, and Hospital Anxiety and Depression Scale was used. Chi-square and independent t tests were used. Results: Among a total of 470 patients, the mean age was 54.1 ± 14.2 years, 284 (60.4%) were female, and 364 (77.4%) were married. About 183 (38.9%) patients had anxiety disorder, and there was a significant association among gender, marital state, occupation, presence of pain, and having gynecological cancers with anxiety. Around 163 (34.7%) of patients had depressive symptoms. The study showed a significant association among gender, occupation, low income, and the presence of a positive family history of cancer, metastasis, and pain with depression. Conclusions: More than one-third of the sample suffered from anxiety and depression; females more than males. There was a significant association between anxiety/depression and gender, occupation, and presence of pain.